Robô Móvel Aplicado a Inspeção em Cabos de Aço de Elevadores Comerciais - Hoffmann, Eder Andrei (2019)
It is known that most of the buildings have elevators, used for the most varied purposes, either for transportation of people and equipment, for eventual changes in apartments and commercial rooms. There is an imminent concern about the state of conservation of the equipment mentioned, in view of the serious accidents that may occur in the event of an inspection carried out by negligent technicians. The place where the greatest difficulty for the inspections is found is the spies, who are responsible for the lift and the displacement. They have difficult access and low light, which makes it more difficult for the technician to periodically maintain the equipment. Given the difficulty and importance of inspecting elevator spies, a system is required that provides greater agility and accuracy in spy inspection. Therefore, it is proposed a device that moves along these spies being controlled by the maintenance technician by means of a remote control, and through a camera, transmit the received data to a software that will show the technician the situation of the spy in real time, facilitating the location of points where there is greater wear of the cable